Synthesis and characterization of a new polyoxometalate nanocluster containing Mo and V as an environmentally green catalyst for oxidative degradation of organic pollutants from aquatic environments. (8th November 2021) - Naslhajian, Hadi; Amini, Mojtaba; Hosseinifard, Mojtaba; Farnia, S. Morteza F.; Janczak, Jan
Abstract: A water‐insoluble Keggin‐type polyoxomolybdovanadate nanocluster, (Et4 N)4 [VMo12 O40 ]·MeCN (1 ) was synthesized and crystallized in acetonitrile. The catalyst was characterized by X‐ray crystallography, UV–Vis, thermogravimetric analysis (TGA), cyclic voltammetry (CV), and FT‐IR techniques. Degradation of organic dyes, Amido black 10B (AB10B) and Methylene blue (MB) was investigated by 1 /H2 O2 system at room temperature and the influence of different conditions on the decomposition of AB10B and MB dyes such as catalyst dosage, oxidant concentration, pH, radical scavengers, and reusability of 1 were studied. Abstract : A water‐insoluble Keggin‐type polyoxomolybdovanadate nanocluster, (Et4N)4[VMo12O40].MeCN (1) was synthesized and used for oxidative degradation of organic pollutants from aquatic environments.